2018
DOI: 10.1007/s12687-018-0360-x
|View full text |Cite
|
Sign up to set email alerts
|

An Internet support group for parents of children with neurofibromatosis type 1: a qualitative analysis

Abstract: Parents of children with neurofibromatosis type 1 (NF1), a rare genetic condition, are at risk for emotional distress. While they may benefit from support groups, they may find it difficult to access support. We conducted an 8-week Internet support group (ISG) with 33 parents (29 mothers, 4 fathers) of children with NF1. Transcripts were evaluated using inductive thematic analysis to determine parental needs and concerns; a process and content theme were identified, with each containing codes and subcodes. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Rosnau et al found that adolescents with NF1 who attended a support group comprised of other similarly affected individuals were associated with higher reported self‐esteem (Rosnau et al., 2017). Studies of an Internet support group for parents of children with NF1 showed this method of support as a feasible and possibly effective option for parental support, and additional studies evaluating qualitative analysis continue (Martin et al., 2016, 2018).…”
Section: Genetic Counseling Processmentioning
confidence: 99%
“…Rosnau et al found that adolescents with NF1 who attended a support group comprised of other similarly affected individuals were associated with higher reported self‐esteem (Rosnau et al., 2017). Studies of an Internet support group for parents of children with NF1 showed this method of support as a feasible and possibly effective option for parental support, and additional studies evaluating qualitative analysis continue (Martin et al., 2016, 2018).…”
Section: Genetic Counseling Processmentioning
confidence: 99%
“…Community support, particularly for individuals with rare diseases such as NF1, can be an important coping resource 43 44. Previous research on online community support platforms for individuals with rare diseases has noted that they are used for both informational and socioemotional support purposes 45 46.…”
Section: Discussionmentioning
confidence: 99%
“…Community support, particularly for individuals with rare diseases such as NF1, can be an important coping resource. 43 44 Previous research on online community support platforms for individuals with rare diseases has noted that they are used for both informational and socioemotional support purposes. 45 46 The value of community support has been identified within the context of cultural and racial socialisation, 47 48 and the study corroborates these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Rietman et al (2018) highlight parent concerns about low motivation and a lack of initiative as possible factors that contribute to this delayed integration into adult living. Similarly, Martin et al (2018) found that parents of youth with NF1 worried about their child's ability to engage in life skills associated with independence including driving, advocating for themselves, and living independently. Future research should explore how clinicians can work with parents and their children to help the AYA develop age‐appropriate skills for independent living.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first known quantitative study to provide preliminary information about the adaptive functioning of AYA with NF1 and pNF tumors during the transition to adulthood. Previous research has focused on more qualitative descriptions of adaptive functioning and the transition experience (Jensen et al, 2019; Martin et al, 2018; Rietman et al, 2018), with another recent study conducting a quantitative evaluation of transition readiness that did not focus exclusively on patients with pNF tumors (Goetsch Weisman et al, 2020). To add to the existing literature, we used objective quantitative data to explore how adaptive skills relate to cognitive and academic variables, as well as relationships between adaptive functioning and educational and employment status, specifically among patients with pNF tumors.…”
Section: Discussionmentioning
confidence: 99%